Conceptual Metaphors In Ritual Communication: The Case Of The Dayak Iban Wedding Mantra - Viktorina Buri; Antonius Totok Priyadi; Patriantoro; Sesilia Seli; Agus Wartiningsih; Ikhza Mahendra Putra (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The Dayak Iban wedding mantra in the Sampi Melah Pinang ritual constitutes a ritual communication practice that constructs cultural meanings concerning married life through metaphorical language. This study analyzes the conceptual metaphors contained in the mantra and examines their functions within the communication context of the wedding ritual. The data, consisting of mantra texts, were obtained from ritual speech events in Kapuas Hulu Regency, West Kalimantan, through observation, in-depth interviews, documentation, and transcription. The analysis was conducted through the identification of metaphorical expressions based on lexical meanings, the mapping of concrete experiences onto abstract concepts, and interpretation within the situational context of ritual communication. The findings identified ten metaphorical expressions organized into eight categories of conceptual metaphors, namely Bonding Metaphor, Protection Metaphor, Journey Metaphor, Life Direction and Control Metaphor, Harmony Metaphor, Family Renewal Metaphor, Social Legitimization Metaphor, and Holistic Well-Being Metaphor. The findings indicate that concrete experiences such as binding, fencing, journeys, direction, physical conditions, kinship, and health are systematically projected onto the abstract concept of married life. Within the ritual context, the mantra is delivered in a sacred setting by a customary leader to the bride and groom, their families, and the community as a medium for invoking blessings and social legitimization through ritual language that reinforces cultural values. Thus, the mantra functions as a collective conceptual construction that represents the way the Dayak Iban community understands and organizes married life.